The Role of Adults on Children Language Acquisition - Meiyanti Nurchaerani; Yessy Nurkita Sari; Haryati Haryati; Syahiid Hidayatullah Rizkyka Hartadhi (English Language Education Study Program of STKIP PGRI Banjarmasin, 2021)
This study aims to notice at the language skills of children from birth to the age of eight years based on the role of adults. The research subject is a boy whom will be known as X, eight years old. This research just focused on X's development of language. Furthermore, children's language acquisition can be categorized into phonology, grammar, semantics, and pragmatics. In collecting data, the authors interviewed one of a friend of the author, named Y. The results of this study indicate the process of language development in children that can be influenced by the role of adults. When the role of adults towards children is not appropriate, then children will experience postpones in language acquisition or postpones in language development in children.